ANALISA PENGELOLAAN MODAL KERJA TERHADAP TINGKAT LIKUIDITAS PADA UD. CAHAYA MANDIRI DI KOTA AMBON - Rumra Suryanti Ismail; Marissa Silooy (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
This study aimed to analyze the influence of working capital management to the level of liquidity in UD. Cahaya Mandiri in the city of Ambon from years 2014-2016. Variables used in this study is the management of working capital and liquidity as the independent variable as the dependent variable. Statistical methods used in this study is a simple linear regression analysis in ad vance of working capital management with measurement tools that turnover of working capital and liquidity analysis measuring devices are used, among others Curren Ratio, Quick Ratio and Cash Ratio. The result showed that the management of working capital have a negative impact and no significant effect on the level of liquidity in the company UD. Cahaya Mandiri in the city of Ambon.Keywords: Working Capital Management, Liquidity and Ratio Analysis